Physical Therapist Practice in the Intensive Care Unit: Results of a National Survey. Issue 10 (1st October 2015) - Malone, Daniel; Ridgeway, Kyle; Nordon-Craft, Amy; Moss, Parker; Schenkman, Margaret; Moss, Marc
Abstract : Background: Early rehabilitation improves outcomes, and increased use of physical therapist services in the intensive care unit (ICU) has been recommended. Little is known about the implementation of early rehabilitation programs or physical therapists' preparation and perceptions of care in the United States. Objective: A national survey was conducted to determine the current status of physical therapist practice in the ICU. Design: This study used a cross-sectional, observational design. Methods: Self-report surveys were mailed to members of the Acute Care Section of the American Physical Therapy Association. Questions addressed staffing, training, barriers, and protocols, and case scenarios were used to determine perceptions about providing rehabilitation. Results: The response rate was 29% (667/2, 320). Staffing, defined as the number of physical therapists per 100 ICU beds, was highest in community hospitals (academic: median=5.4 [range=3.6–9.2]; community: median=6.7 [range=4.4–10.0]) and in the western United States (median=7.5 [range=4.2–12.9]). Twelve percent of physical therapists reported no training. Barriers to providing ICU rehabilitation included insufficient staffing and training, departmental prioritization policies, and inadequate consultation criteria. Responses to case scenarios demonstrated differences in the likelihood of consultation and physical therapists' prescribed frequency and intensity of care based on medical interventions rather than characteristics of patients. Physical therapists in academic hospitals were more likely to be involved in the care of patients in each scenario and were more likely to perform higher-intensity mobilization. Limitations: Members of the Acute Care Section of the American Physical Therapy Association may not represent most practicing physical therapists, and the 29% return rate may have contributed to response bias. Conclusions: Although staffing was higher in community hospitals, therapists in academic and community hospitals cited insufficient staffing as the most common barrier to providing rehabilitation in the ICU. Implementing strategies to overcome barriers identified in this study may improve the delivery of ICU rehabilitation services.